Bodies of violence: theorizing embodied subjects in international relations - Wilcox, Lauren B. (Oxford studies in gender and international relations, 2015)
Chapter 1: Bodies, Subjects, and Violence in International Relations 17. - Chapter 2: Dying is Not Permitted: Guantánamo Bay and the Liberal Subject of IR 49. - Chapter 3: Explosive Bodies: Suicide Bombing as an Embodied Practice and the Politics of Abjection 80. - Chapter 4: Crossing Borders, Securing Bodies: Airport Security Assemblages and Bodies of Information 104. - Chapter 5: Body Counts: The Politics of Embodiment in Precision Warfare 131. - Chapter 6: Vulnerable Bodies and "Responsibility to Protect" 166